2023
DOI: 10.3390/rs15030637
|View full text |Cite
|
Sign up to set email alerts
|

GNSS-R Observations of Marine Plastic Litter in a Water Flume: An Experimental Study

Abstract: Currently, eight million metric tons of plastic end up in the oceans every year, and microplastics in different forms are present in almost all water systems in the world: streams, rivers, lakes, or oceans, and even in our blood. Detection of marine litter is an urgent task. Some works have recently reported the potential of GNSS-Reflectometry to detect marine plastic litter from space. This study presents the results of a controlled field experiment conducted under the auspices of ESA at the “Atlantic Basin” … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Figure 24) (Evans & Ruf, 2021). In addition, the experimental study used statistical analysis of the reflectivity (phase and amplitude) with a very short integration time and was conducted to detect the accumulation of marine plastic litter (Gonga et al, 2023), while the analysis of the change observed in the reflected power did not show significant results.…”
Section: Microplasticsmentioning
confidence: 99%
“…Figure 24) (Evans & Ruf, 2021). In addition, the experimental study used statistical analysis of the reflectivity (phase and amplitude) with a very short integration time and was conducted to detect the accumulation of marine plastic litter (Gonga et al, 2023), while the analysis of the change observed in the reflected power did not show significant results.…”
Section: Microplasticsmentioning
confidence: 99%
“…da Costa et al [121] used a wideband RADAR, 2-20 GHz, showing the capability of the system to detect the plastic for several combinations of plastic concentrations and wave conditions. Gonga et al [122] implemented a global navigation satellite system reflectometry (GNSS-R) setup. GNSS-R is a bistatic RADAR technique which uses satellite navigation signals at the L-band as the transmitter and a receiver installed in a different platform.…”
Section: Radarmentioning
confidence: 99%